2020
DOI: 10.1097/gox.0000000000002637
|View full text |Cite
|
Sign up to set email alerts
|

No-drain Technique in Abdominal Closure for Breast Reconstruction: Lower Complication Rate, Shorter Hospitalization Stay

Abstract: Background: Progressive tension suture (PTS) technique in cosmetic abdominoplasty is safe in terms of seroma rates. This was extrapolated to deep inferior epigastric perforator (DIEP) flap donor site closure. No study to our knowledge has analyzed the PTS technique alone without drains in transverse rectus abdominis musculocutaneous (TRAM) flap donor sites. We aim to show that no-drain closure has similar complication rates and this may be applied to TRAM flaps safely even though they have higher d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…In addition to preoperative optimization, the use of enhanced recovery after surgery (ERAS) programmes (ERP) throughout the patient pathway have been shown by a systematic review by Soterupulos et al to reduce both the length of stay and analgesia requirements [25]. In addition to patient education, multimodal analgesia, VTE and antibiotic prophylaxis, early drain removal by postoperative day 3 as advocated by many authors (Chan et al, Miranda et al) coupled with active mobilisation are important parts of the ERAS programmes [1,14]. Avoiding drain use in the first instance by utilising PTS can further contribute to patient progress in terms of time to first walk, reducing the length of hospital stay and minimising the complications reported above.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to preoperative optimization, the use of enhanced recovery after surgery (ERAS) programmes (ERP) throughout the patient pathway have been shown by a systematic review by Soterupulos et al to reduce both the length of stay and analgesia requirements [25]. In addition to patient education, multimodal analgesia, VTE and antibiotic prophylaxis, early drain removal by postoperative day 3 as advocated by many authors (Chan et al, Miranda et al) coupled with active mobilisation are important parts of the ERAS programmes [1,14]. Avoiding drain use in the first instance by utilising PTS can further contribute to patient progress in terms of time to first walk, reducing the length of hospital stay and minimising the complications reported above.…”
Section: Discussionmentioning
confidence: 99%
“…Chan et al: They performed a single-centre retrospective review of 50 patients undergoing DIEP and transverse rectus abdominis (TRAM) flap reconstructions [14]. The TRAM flap reconstructions included muscle-sparing free TRAM (3), free TRAM (17), and pedicled TRAM flap (4).…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Thacoor et al have reported that drain-free abdominal closure in DIEP flap breast reconstruction could be safely achieved without increased postoperative complications [ 5 ]. No-drain techniques for DIEP flap donor site closure reportedly had a lower complication rate than the conventional abdominal drainage technique [ 6 , 7 ]. Meanwhile, a report has recommended the placement of CSD for breast reconstructions with a transverse rectus abdominis muscle (TRAM) flap [ 8 ].…”
Section: Introductionmentioning
confidence: 99%